2021
DOI: 10.1002/fsn3.2686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different phosphorus‐free water‐retaining agents on the quality of frozen tilapia fillets

Abstract: Tilapia is an economically important fish worldwide, but its quality is affected by storage practices. To improve the quality of tilapia fillets during frozen storage, we examined the effect of pretreatment with various combinations of different concentrations of trehalose, potassium bicarbonate, and chitosan. Following pretreatment, we analyzed the tilapia fillets using quality indicators, including soaking weight gain, coating weight gain, water‐holding capacity, thawing loss, pH, Ca2+‐ATPase activity, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The non-phosphorus water retention agent has many benefits, including diverse varieties, excellent safety, high efficiency, and degradability. It can be one of the substances such as sugar, amino acids, proteins, and non-phosphorus salts, or it can be the same as phosphate, which can be formed by a variety of substances through the compounding of complementary effect of compound non-phosphorus water retention agent (Li et al, 2022c). (Peng et al, 2023) discovered that the hydrolysis product of whey protein had inhibitory effects on the degradation of meat MP.…”
Section: Non-phosphorus Water Retention Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-phosphorus water retention agent has many benefits, including diverse varieties, excellent safety, high efficiency, and degradability. It can be one of the substances such as sugar, amino acids, proteins, and non-phosphorus salts, or it can be the same as phosphate, which can be formed by a variety of substances through the compounding of complementary effect of compound non-phosphorus water retention agent (Li et al, 2022c). (Peng et al, 2023) discovered that the hydrolysis product of whey protein had inhibitory effects on the degradation of meat MP.…”
Section: Non-phosphorus Water Retention Agentsmentioning
confidence: 99%
“…(Zhu et al ., 2023a) found that water‐soluble citrus fibres could enhance polysaccharide–protein interactions or protein–protein interactions to form a relatively tight mesh structure, thereby improving the gel strength and water retention capacity of lamb MP gels. (Li et al ., 2022c) studied the water retention and quality of tilapia and found that a mixture of 4% alginate, 1.2% KHCO 3 , and 0.2% chitosan gave the best results. Additionally, it has been shown that compounds with comparable properties but varying molecular weights exhibit variations in their capacity to maintain moisture in meat.…”
Section: Meat Water Retention Technologymentioning
confidence: 99%
“…4: (I) The majority of SWRAs include hydroxyl and carbonyl groups, and some also contain amino, imino, acyl, and other hydrophilic groups. These hydrophilic groups can form hydrogen bonds with water molecules, which support the excellent WHC of SWRA; (II) On the surface of meat products, polysaccharides combine with calcium or magnesium ions to form a protective film, which protects the original spatial structure of actomyosin and stabilizes the moisture inside the meat [57]; (III) Polysaccharides of different molecular weight can penetrate into meat products muscle by capillary force and other actions, and interact with proteins to expand the space between muscle fibers [2], for example, with a positive charge group of polysaccharides, such as CS can combine with proteins to increase the space between myofibril, myofibrils and lessen water-soluble protein loss [25]; (IV) They could create a strong three-dimensional network with calcium/magnesium chelating to capture the water [58];…”
Section: Swra For Excellent Whcmentioning
confidence: 99%
“…P. Chantarasataporn et al [93] Drip loss, thiobarbituric acid reactant, aerobic plate number, pH value and total volatile basic nitrogen are lower. Furthermore, Li et al [25] studied the synergistic effect of different concentrations of TR, potassium bicarbonate and CS on the WHC of tilapia fillets, and studied the tilapia fillets after frozen storage for 3 months. With the increase of TR concentration, the thawing loss rate decreased significantly from 9.18% to 6.60% and KHCO3 1.0% increased the weight of fish fillets by 3.41%.…”
Section: Trehalose (Tr) and The Derivativesmentioning
confidence: 99%
See 1 more Smart Citation